Bringing Multi-Criteria Decision Making into cell identification for Shoreline Management Planning in a coastal city of Southeast China. (15th June 2021) - Li, Xun; Huang, Jinliang; Tu, Zhenshun; Yang, Shunliang
Abstract: Recent shoreline management efforts have extended the scope of management plan to address multi-stakeholders' conflicts over the use of coastal resources and their preservation. As cell identification is a critical step towards the development of Shoreline Management Plan (SMP), this paper provides the needed evidence to justify its rationality using Longhai city as a testing site. The coastal zone boundary of Longhai city was firstly defined taking into consideration the interface between land and sea. Seven cell units were identified with due consideration of existing plans. Subsequently, Multi-criteria Decision Making analysis coupled with GIS techniques was performed to verify the rationality of the cell identification. The results justified and supported the cell identification approach and outcomes with respect to dominant sectors within each unit, as well as the integrative and adaptive characteristics of the SMP in balancing environmental conservation and socioeconomic development. The quantitative approach further enables evaluating its adaptability in a changing environment. Highlights: A systematic coastal planning is required in Longhai in line with the Integrated Coastal Management practice in Xiamen. A more integrative planning in consideration of various terrestrial and marine plans is required in coastal area. Cell identification is a critical step in Shoreline Management Plan so as to make executable plan for each cell. Multi-Criteria Decision Making is a powerful tool to testify the rationality of the planning outcomes.